The Political Economy of Fisheries Development During Joko Widodo’s Regime - Nasution, Anta Maulana; Wicaksono, Viga Ananda (Politika: Jurnal Ilmu Politik, 2023)
The article discusses the political economy of fisheries development in Indonesia and its dynamics during Joko Widodo's regime. The development of the fisheries sector, particularly marine fisheries, has faced ups and downs since Indonesia's independence. During the New Order era, fisheries development depended on foreign investment and international aid, which on several occasions has driven severe conditions in depleted fish stocks and the marginalization of small-scale fishermen. The fisheries sector began to be measured politically after the reform period when Indonesia established the Department/Ministry of Marine Affairs and Fisheries. Even so, the direction of fisheries development has not met its consistency. When Joko Widodo served as president, he created a big vision for maritime development, namely "Global Maritime Axis," where the fisheries sector became one of the national development priorities. Jokowi appointed Susi Pudjiastuti as Minister of Marine Affairs and Fisheries (MAF). Under Susi, the development of fisheries began to be reformed and she enacted many strict policies to deal with fisheries problems that have been occurring for decades. Susi gained many political pressures because her strict policies disrupted the oligarchic system that had controlled fisheries resources at the time. Fisheries development experienced inconsistencies from the last of 2019 until the end of 2020 because the first Minister of MAF in Jokowi's second period made contradictory policies from Susi's period. Since 2021, Indonesia's fisheries development has been using a blue economy model implemented through the regulation on measured fishing.